PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) BERBANTUAN MEDIA QUIZALIZE TERHADAP MINAT DAN HASIL BELAJAR GEOGRAFI SISWA KELAS XI SMA NEGERI 1 BATIPUH - Octav Faria Nanda; Sri Mariya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Think Pair Share (TPS) learning model assisted by Quizalize interactive media on the learning interest and learning outcomes of geography of class XI students of SMA Negeri 1 Batipuh. This study uses a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. This type of research is experimental research using a purposive sampling technique. The research sample consisted of two classes, namely the experimental class XI Geografi 4 which was given treatment using the TPS model assisted by Quizalize interactive media, and the control class XI Geografi 1 which used the conventional method. Data collection used a learning interest questionnaire and a multiple-choice pretest-posttest instrument. The results showed that the TPS model assisted by Quizalize interactive media had a significant effect on students' learning interest, with the average final questionnaire score of the experimental class of 84.74 being higher than the control class of 65.32, and a significance value of 0.000 < 0.05. In addition, learning outcomes also experienced a significant increase, indicated by the average posttest score of the experimental class of 81.32 being higher than the control class of 65.59, with a significance value of 0.000 < 0.05 and an N-Gain value of 68.87% which is categorized as quite effective, higher than the control class of 46.72% which is categorized as less effective. A multivariate analysis (MANOVA) further confirmed that the TPS model assisted by Quizalize had a simultaneous significant effect on both learning interest and learning outcomes together (Wilks' Lambda = 0.067; F = 453.095; Sig. = 0.000). Thus, the TPS model assisted by Quizalize has been proven to be able to significantly increase learning interest and learning outcomes in geography, both separately and simultaneously.